Molecular Evidence of Bartonella Species in Ixodid Ticks and Domestic Animals in Palestine - Ereqat, Suheir; Nasereddin, Abdelmajeed; Vayssier-Taussat, Muriel; Abdelkader, Ahmad; Al-Jawabreh, Amer; Zaid, Taher; Azmi, Kifaya; Abdeen, Ziad (Frontiers in Microbiology, 2016)
Ticks play an important role in disease transmission as vectors for human and animal pathogens, including the Gram-negative pathogen Bartonella. Here, we evaluated the presence of Bartonella in ixodid ticks and domestic animals from Palestine. We tested 633 partly engorged ticks and 139 blood samples from domestic animals (dogs, sheep and camels) for Bartonella using ITS-PCR. Bartonella DNA was detected in 3.9% of the tested ticks. None of the ticks collected from sheep and goats were positive for Bartonella. Seventeen R. sanguineus ticks (17/391; 4.3%) collected from dogs were infected with B. rochalimae (n=10), B. chomelii (n=6), and B. koehlerae (n=1). Four H. dromedarri ticks (4/63; 6.3%) obtained from camels were infected with B. bovis (n=2) and B. rochalimae (n=2). Among canine blood samples (n=110), we found one asymptomatic female dog to be infected with B. rochalimae (0.9%). The detection of zoonotic Bartonella species in this study should raise awareness of these vector-borne diseases among physicians, veterinarians and public health workers and highlight the importance of surveillance and preventive measures in the region.